Comparative Studies Using Communicative English Summary M0365 in EFL - Ima Masofa; Irwan Sumarsono (INTERACTION: Jurnal Pendidikan Bahasa, 2022)
This study is a comparative research that focuses on the similarities and differences of two teachings English using MO365, namely comparison using communicative English summary. Researchers analyse the similarities in two teachings using communicative English summary in MO365 to achieve good score. The differences are researches conduct research in two different classes, responses and dates. This research uses qualitative method, which was based on student’s achievement in M0365.The results of this study can be formulated as follows. 1) Both have similarities that they study comparison;(2) Both that students who apply communicative English summary in MO365 can easily answer questions and get good score in M0365.3) Differences are researchers who conduct research in two different students classes and dates. The researcher has conducted a study on the title comparative studies using communicative English summary MO365 in EFL that the main objective of the study is to compare two classes that the students achieve good scores when they use English summary in MO365 that can be used in online English teaching.